Creative Work Beyond the Creative Industries: Innovation, Employment and Education - Rodgers, Jess; Hearn, Greg; Goldsmith, Ben; Bridgstock, Ruth (Cheltenham, UK Edward Elgar, 2014)
'Hearn and his colleagues have amassed an impressive array of empirical evidence, theoretical insights and policy prescriptions for understanding how creative workers are contributing to a variety of industries outside the purely cultural or creative industry sectors. The scope of their investigations includes healthcare, banking, manufacturing, digital technology, creative services, journalism, media and communication, and higher education. This book significantly advances our understanding of how creative workers are utilizing their capabilities to contribute broadly to the economy.
Cover; Copyright; Contents; Figures; Tables; Contributors; Acknowledgements; 1. Creative work beyond the Creative Industries: an introduction; PART I Foundational issues; 2. Creative labour and its discontents: a reappraisal; 3. Compensating differentials in Creative Industries and occupations: some evidence from HILDA; 4. Creative digital services in education, mining and manufacturing: pursuing innovation through interoperability; 5. London's creative workforce; PART II Case studies of embedded creative employment; 6. Embedded creatives in Australian healthcare --<U+000d><U+000a>an update 7. Embedded creatives in the Australian manufacturing industry8. Embedded digital creatives; 9. Embedded digital creative workers and Creative Services in banking; 10. Looking inside the portfolio to understand the work of creative workers: a study of creatives in Perth; PART III Education, learning and careers; 11. Learning processes in Creative Services teams: towards a dynamic systems theory; 12. Translating creative skills: an example of Youthworx Media for marginalized youth; 13. Developing agency in the creative career: a design-based framework for work integrated learning
Keywords: Empresas -- Creación; Creatividad; Innovaciones tecnológicas; Industria